Interplay Between Depression, Anxiety, and Working Memory among Students in College of Medical Sciences Ahmadu Bello University Zaria Nigeria (Nigerian Journal of Physiological Sciences, 2025)
University life presents a mix of academic and social challenges that often contribute to stress and mental health issues. Chronic stress, particularly in university students, is a well-known risk factor for depression and anxiety, which can lead to cognitive impairments such as deficits in working memory. This study explored the prevalence of depression and anxiety among students at the College of Medical Sciences, Ahmadu Bello University, Zaria, Nigeria, and examined their impact on working memory. A cross-sectional approach was used, involving undergraduates from different levels and departments within the college. Participants completed the Beck Depression Inventory (BDI) and Generalized Anxiety Disorder-7 (GAD-7) scale to assess symptoms of depression and anxiety, while the 2-back task evaluated working memory performance. Findings revealed a high prevalence of depressive (47.84%) and anxiety (65.12%) symptoms among students. However, no significant relationship was found between these symptoms and working memory performance (p > 0.05). Students experiencing anxiety were 12 times more likely to develop depression, highlighting the strong co-occurrence of these conditions (p = 0.00). Age did not have a significant effect on these results. These results emphasize the urgent need for increased mental health awareness and accessible support services for university students to reduce the impact of depression and anxiety on academic performance and overall well-being.